AKT POŚWIĘCENIA NARODU POLSKIEGO NIEPOKALANEMU SERCU MARYI WEDŁUG SŁUGI BOŻEGO KARDYNAŁA AUGUSTA HLONDA - Bachanek, Grzegorz (Studia Theologica Varsaviensia, 2018)
In 1946, after the end of the II World War, in view of the menaces linked to communist atheism an act of entrustment of the nation to the Immaculate Heart of Our Lady was performed on the initiative of the Primate of Poland August Hlond. Looking at the origins of the event, on the one hand we can see the reference to the oath of King John II Casimir Vasa, and on the other hand to the revelations of Fatima, which are an encouragement to entrust humanity to the Immaculate Heart of Mary. A. Hlond sees the urgency of moral and religious renewal of the nation in the times of damages caused by war and new dangers linked to communist atheism. Choices made by Poland and Poles have a particular meaning for our Slavic neighbours and the whole world. In the period of violent political changes, A. Hlond looks at the future of the Church, Poland and the world with hope. It is Mary who can secure the future and protect the Church from the powers of darkness and bring victory.